Royalties for peace in the social inclusion and reconciliation sector (2024)
This document develops a general description about the investment projects executed with resources from the General Royalties System (SGR), with a focus on the social inclusion and reconciliation sector, after the 2016 peace agreement, starting from a normative and descriptive framework of the execution of the resources allocated to the sector before between the years 2018 and 2024, with the objective of performing an analysis of the current execution that allows us to conclude the contribution of such resources from the SGR to the post-conflict in Colombia, likewise determining the coherence of the execution with the Social Inclusion sector, but especially reconciliation.